PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA MATERI PENCERMINAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 SDN 2 SUNTENJAYA: Penelitian Tindakan Kelas Pembelajaran Matematika di kelas IV SDN 2 Suntenjaya DesaSuntenjaya Kecamatan Lembang - Rabbani, Silvya (2013)
PenelitianTindakanKelasinidilatarbelakangikesulitan guru dan peserta didik dalampem belajaran matematika materi pencerminan di kelas 4 SDN 2 Suntenjaya. Kesulitan guru dalampembelajaran, terlihatdari rata-rata hasilbelajarpesertadidik yang masihrendahyaitu 60 dengan KKM 68. Guru sulitmenentukanteknik, metode danpendekatan yang tepatuntukpembelajaranmatematikamateripencerminan. Sedangkansiswasulitmemahamikonseppencerminan yang dijelaskan secara abstrak olehgurunyasehinggamempengaruhihasilbelajar. Salah satu pendekatan untukmeningkatkanhasilbelajarsiswaadalahpendekatanpembelajarankontekstual. pendekatanpembelajarankontekstualmerupakansalahsatupendekatan yang mengaitkanmateri yang diajarkandengankehidupansehari-hari. Dengan menerapkan pendekatan pembelajarankontekstual, pembelajaran matematika materi pencerminandapatdilaksanakansecarakontekstual agar pesertadidik dapatlebihmemahanikonseppencerminan. Tujuanpenelitianiniadalahmengungkappeningkatanhasilbelajarpesertadidikkelas IV di SDN 2 Suntenjayapadamateripencerminanmelaluipenerapanpendekatanpembelajarankontekstual. PenelitianTindakanKelas (PTK) initerdiridariduasiklus. Tiapsiklusterdiridariempatkegiatan, terdiridari: perencanaanpembelajaran, pelaksanaanpembelajaran, kegiatanobservasidanrefleksi. Dalam PTK inipenelitimelibatkanduatemansejawatdansatu guru kelas IV untukmenjadi observer dalamkegiatanpelaksanaanpembelajaran. Subjekpenelitianadalahsiswakelas IV SDN Suntenjaya yang berjumlah 33 orang. Padateshasilbelajarterdapatpeningkatanhasilbelajar yang signifikandarisetiapsiklusnya. Data yang didapatdaritesdanhasilobservasidianalisis. Dari hasil test diperoleh rata-rata skor 83.87. Skortersebutmelebihi KKM matapelajaranmatematikayaitu 68. Dari hasilobservasiterjadipeningkatanaktivitas guru danaktivitaspesertadidikkearahpositifdalamkegiatanpembelajaran. Dengandemikianmenunjukanbahwapendekatanpembelajarankontekstualdapatmeningkatkanhasilbelajarpesertadidikpadamateripencerminan di kelas IV SDN 2 Suntenjaya. Kata Kunci :PendekatanPembelajaranKontekstual, Pencerminan, danHasilBelajar Classroom Action Research is motivated difficulty teachers and learners in the learning of mathematics reflection material in grades 4 SDN 2 Suntenjaya. Teachers in learning difficulties, seen from the average learning outcomes of students were still low at 60 with KKM 68. Teachers difficult to determine the techniques, methods and approaches appropriate for teaching mathematics reflection material. While students understand difficult concepts described in the abstract reflections by his teacher that affect learning outcomes. One approach to improving student learning outcomes are contextual learning approach. contextual learning approach is one approach that links the material being taught with daily activity. By applying contextual learning approach, the learning material mathematics contextually reflection material can be implemented so that learners can be understanding concept of reflection. The purpose of this study is to reveal an increase in the study of students in the fourth grade at SDN 2 Suntenjaya reflection of the material through the application of contextual learning approach. Classroom Action Research is composed of two cycles. Each cycle consists of four activities, consisting of: lesson planning, lesson implementation, observation and reflection. In this Classroom Action Research involves two peers and one fourth grade teacher to become an observer in the implementation of learning activities. Subjects were fourth grade students at SDN 2 Suntenjaya which totaled 33 students. On achievement test contained a significant increase in learning outcomes of each cycle. Data obtained from tests and observations were analyzed. From the test results obtained by an average score of 83.87. The score exceeds the minimal score mathematics courses is 68. From the observation of an increase in activity of teachers and learners activities in a positive direction in learning activities. This is showing that the approach to contextual learning can improve learning outcomes of students in the fourth grade reflection material in SDN 2 Suntenjaya. Keywords: Contextual Teaching Learning Approach, Reflection, and Result of Learning